Hepatocellular Carcinoma Cells Are Protected From Immunolysis by Mesenchymal Stromal Cells Through Indoleamine 2,3 Dioxygenase - Raghavan Chinnadurai (Frontiers Media S.A., 2021)
B7 family proteins serve as checkpoint molecules that protect tumors from T cell mediated lysis. Tryptophan degrading enzymes indoleamine 2,3 dioxygenase (IDO) and tryptophan 2,3 dioxygenase (TDO) also induce T cell immune tolerance. However, little is known about the relative contribution of B7 molecules, tryptophan degrading enzymes, as well as the impact of tumor and stromal cell interactions to the development of immunosuppressive tumor microenvironment. To investigate such interactions, we used a tripartite model of human hepatocellular carcinoma cell line (HepG2) and mesenchymal stromal cells (MSCs) co-cultured with peripheral blood mononuclear cells (PBMCs). Co-culture of HepG2 cells and activated PBMCs demonstrate that HepG2 cells undergo PBMC mediated cytolysis, despite constitutive expression of B7-H3 and upregulation of PD-L1 by IFNγ. Knockdown of B7-H3, PD-L1 or IDO does not modulate PBMC mediated lysis of HepG2 cells. However, TNFα preactivation enhances lysis of HepG2 cells, and blocking of TNFα production from PBMCs protects HepG2 cells. On the other hand, MSCs protect HepG2 cells from PBMC mediated lysis, even in the presence of TNFα. Further investigation showed that MSC mediated protection is associated with the unique secretome profile of upregulated and downregulated cytokines and chemokines. IFNγ activated MSCs are superior to TNFα activated or control MSCs in protecting HepG2 cells. Blockade of IFNγ driven IDO activity completely abolishes the ability of MSCs to protect HepG2 cells from cytolysis by PBMCs. These results suggest that inhibition of IFNγ activation of IDO induction in stromal cells, combined with usage of TNFα, could be a novel immunotherapeutic strategy to induce regression of hepatocellular carcinoma.